Dilution and dividend effects on the portuguese equity warrants market - Correia, José Eduardo (2008)
The aim of this study is to analyse the impact of dilution and dividends on the goodness of fit of warrant pricing valuation models, to the Portuguese warrants market. In order to avoid modelling bias over the research design, and to test dividend and dilution effects we decided to keep this.empirical research under the Black-Scholes framework. Therefore,four pricing models were used: the original Black-Scholes model and three derivations. Using these four models we empirically estimate values for actual warrant prices, computing the mean percentage error for each (the difference between model prices and market prices). We found that the original Black-Scholes model when adjusted to account for dilution as well as for dividends works best in the Portuguese market. The analysis uses data collected from the Euronext Lisbon, between 1998 and 2000.